Integrated analysis of the multifunctional protein Aft1p - Berthelet, Sharon (University of Ottawa (Canada), 2008)
The Saccharomyces cerevisiae transcription factor Aft1p has an established role under iron-deplete conditions in the induction of genes involved in iron acquisition and utilization. Recent studies have indicated that Aft1p is required for faithful chromosome transmission and aft1Delta mutant cells have defects in cell cycle progression. This suggests that Aft1p has additional, but undefined, cellular roles under iron-replete conditions. To explore the role of Aft1p, two genome-wide screens were utilized to identify nonessential deletion mutants that are unable to tolerate defects in Aft1p function, and an Aft1p physical protein-protein interaction map was constructed using affinity purification and mass spectrometry. Our integrative analysis has produced an extended network of genetic and physical interactions, which connect Aft1p to a wide range of cellular functions including the RIM101 pH response pathway, DNA replication, and DNA repair. Our results establish that Aft1p is multifunctional with broad cellular roles.
Keywords: Chemistry, Biochemistry.